Heterogeneous effects of high school peers on educational outcomes - Silvia Mendolia; Alfredo R. Paloyo; Ian Walker (Rheinisch-Westfälisches Institut für Wirtschaftsforschung (RWI), 2016)
We investigate the relationship between peers' abilities and educational outcomes at the end of high school using data from the rich Longitudinal Study of Young People in England (LSYPE) matched to the National Pupil Database of children in state schools in England. In particular, we focus on the effect of peers' abilities, measured through achievements in Key Stage 3 (Age 14), on high powered test scores at Ages 16 and 18, and on the probability of attending university. Our identification strategy is based on a measure of the peers of peers' ability. In particular, for each individual, we look at her high school peers and select their primary school peers who do not attend the same high school and who did not attend the same primary school as the individual. We then use peers-of-peers ability, measured using Age 11 test scores as an instrument for high school average peer ability, measured using Age 14 test scores. We also use quantile regression to explore the effect of peers' ability on different parts of the distributions of the outcomes. Our results show that average of peers' abilities has a moderate positive effect on test scores at Ages 16 and 18, and that being in a school with a large proportion of low-quality peers can have a significantly detrimental effect on individual achievements. Furthermore, peers' ability seems to have a stronger effect on students at the bottom of the grade distribution, especially at Age 16. – – Durch die Zusammenführung des "Longitudinal Study of Young People in England" (LSYPE) Datensatzes und des "National Pupil Database" Datensatzes soll der Zusammenhang von Begabung im Umfeld des Schülers und dessen schulischen Leistungen untersucht werden. Insbesondere konzentriert sich die Untersuchung auf den Effekt von der Begabung des Umfeldes - messbar durch Testergebnisse der (Mit-)Schüler im Alter von 14 Jahren - auf die Wahrscheinlichkeit des Besuchs einer Universität, bzw. auf Testergebnisse im Alter von 16 und 18 Jahren. Die Identifikationsstrategie basiert auf der Messung der Begabung des Umfeldes des Umfeldes der Schüler. Im Speziellen wird das Umfeld derjenigen Schüler, die zusammen mit einem Individuum die High School besucht haben, beleuchtet, indem Schüler ausgewählt werden, die mit diesen - jedoch nicht mit dem Individuum - die Grundschule, jedoch nicht die High School besucht haben. Diese "peers-of-peers" Begabung wird genutzt, indem Testergebnisse im Alter von 14 Jahren mit Testergebnissen im Alter von elf Jahren instrumentiert werden. Weiterhin werden Quantilsregressionen genutzt, um die Höhe des Einflusses von Mitschülern an verschiedenen Punkten der Ergebnisverteilung herauszuarbeiten. Die Ergebnisse zeigen, dass die Begabung der Mitschüler einen leichten Einfluss auf die Testergebnisse mit 16 bzw. 18 Jahren hat. Besonders groß ist der negative Einfluss auf die Ergebnisse eines Individuums an einer High School mit einem hohen Anteil vergleichsweise "schlechter" Mitschüler. Weiterhin konnte ein stärkerer Effekt auf Schüler am unteren Ende der Notenverteilung festgestellt werden, insbesondere im Alter von 16 Jahren.
Keywords: I20; J24; 330; peer effects; instrumental variables; test scores